2006
DOI: 10.1038/sj.bmt.1705388
|View full text |Cite|
|
Sign up to set email alerts
|

Does younger donor age affect the outcome of reduced-intensity allogeneic hematopoietic stem cell transplantation for hematologic malignancies beneficially?

Abstract: Sixty three patients aged 27-66 years (median 52) were allografted from HLA-matched sibling (n ¼ 47), 10 of 10 allele-matched unrelated (n ¼ 19), or one-antigen/allelemismatched (n ¼ 7) donors aged 24-69 years (median 46) after a conditioning regimen comprising 100 mg/m 2 melphalan. Cyclophosphamide (50 mg/kg) was also administered to patients who had not been autografted previously. Cyclosporine or tacrolimus, and mycophenolate mofetil were administered to prevent graft-versus-host disease (GVHD). The 2-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
(19 reference statements)
0
37
1
Order By: Relevance
“…Differences are, however, not statistically significant. If new results showed that effects of donor age on transplantation success were smaller than demonstrated so far, [11][12][13][14] the preference of transplant physicians for younger donors could decline. As a result, both differences in age-specific donation probabilities and the number of donors who must be recruited to compensate for donor file aging would decrease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences are, however, not statistically significant. If new results showed that effects of donor age on transplantation success were smaller than demonstrated so far, [11][12][13][14] the preference of transplant physicians for younger donors could decline. As a result, both differences in age-specific donation probabilities and the number of donors who must be recruited to compensate for donor file aging would decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Such preferences are in accordance with published results indicating more favorable transplantation outcomes for transplants that use younger donors. [11][12][13][14] The calculated donation probabilities provide the input for a model aimed to quantify the aging-induced reduction of donor file usefulness and to estimate the number R of donors who need to be recruited to compensate for this reduction. It shows that R exceeds the number of donors who reach the age limit considerably in both analyzed scenarios (intermediate typing of the HLA-A and -B loci versus more complete typing of new donors).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34][35][36] However, few studies have assessed the combined effect of donor age and type on outcome. Some studies have suggested more favorable outcome after transplant with young MUD as compared with older MRD.…”
Section: Discussionmentioning
confidence: 99%
“…Donor's age has been previously studied in both myeloablative and non-myeloablative allogeneic transplant conditioning settings. 29,30 It has been hypothesized that as a donor's age increases, both repopulation and homing abilities of the donor stem cells become impaired. 31,32 Donor's T lymphocytes are also affected by telomere shortening and decreased effector activity.…”
Section: % Overall Survivalmentioning
confidence: 99%